PERFECTION OF ACTIVITY OF MEASURING (TESTING) LABORATORIES WITH THE USE OF KNOWLEDGE MANAGEMENT SYSTEMS - K. A. Pavlov; P. S. Serenkov; V. A. Nifagin (Приборы и методы измерений)
The question of necessity of development and implementation of the Knowledge management system within the accredit measuring (testing) laboratory is being discussed. The conception offered is the methodlogy of expert system creation based upon ontologies for subjective areas of activities in the measuring (testing) laboratory, built on the base of process approach with the module principle.